If G(x)=−25−x then limx→1 G(x)−G(1)x−1 has the value 

If G(x)=25x then limx1G(x)G(1)x1 has the value 

  1. A

    12.4

  2. B

    15

  3. C

    24

  4. D

    1/5

    Register to Get Free Mock Test and Study Material

    +91

    Verify OTP Code (required)

    I agree to the terms and conditions and privacy policy.

    Solution:

    We have,

    limx1G(x)G(1)x1=G(1)    [By def. of derivative]

    Now,

    G(x)=25x2G(x)=x25x2G(1)=124

    Chat on WhatsApp Call Infinity Learn

      Register to Get Free Mock Test and Study Material

      +91

      Verify OTP Code (required)

      I agree to the terms and conditions and privacy policy.